Early childhood theories today - Bradbury, Aaron; Swailes, Ruth (London Learning Matters, 2022)
"If you work in the early years, you have probably heard of Montessori and Bronfenbrenner - but have you heard of Bavolek or Fisher? Contemporary theorists and theories of early childhood learning have much to teach us. It is often forgotten that this learning is still evolving and that new voices are joining the discussion every year. This book introduces early years practitioners to some contemporary theorists and explores their work alongside more well-known thinkers. It demonstrates how these theories relate to everyday practice in the early years and that discussion of them can support ongoing professional learning." --
Introduction -- 1. Stephen Bavolek / Aaron Bradbury -- 2. Urie Bronfenbrenner (1917-2005) / Tamsin Grimmer -- 3. Pierre Bourdieu (1930-2002) / Kate Irvine -- 4. Friedrich Froebel (1782-1852) / Meredith Rose -- 5. Julie Fisher / Ruth Swailes -- 6. Loris Malaguzzi (1920-1994) / Valerie Daniel -- 7. Maria Montessori (1870-1952) / Sue Allingham -- 8. Tina Bruce / Philippa Thompson -- 9. Valerie Daniel / Aaron Bradbury -- 10. Margaret McMillan and Grace Owen : nursery wars : debating and defining the modern nursery / Pam Jarvis.
Includes bibliographical references (pages 137-144) and index.
Keywords: Early childhood education -- Philosophy